2010
DOI: 10.1111/j.1574-6976.2009.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Common trends in mutualism revealed by model associations between invertebrates and bacteria: Table 1

Abstract: Mutually beneficial interactions between microbes and animals are a conserved and ubiquitous feature of biotic systems. In many instances animals, including humans, are dependent on their microbial associates for nutrition, defense, or development. To maintain these vital relationships animals have evolved processes that ensure faithful transmission of specific microbial symbionts between generations. Elucidating mechanisms of transmission and symbiont specificity has been aided by the study of experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 201 publications
(298 reference statements)
1
99
0
Order By: Relevance
“…The egg mucus interface probably facilitated attraction, accumulation and host recognition of epibionts for horizontal transmission. This epibiont transmission pathway is in adequacy with the large colonization of the MAR by R. exoculata because horizontal transmission is supposed to promote dispersal as compared with vertical transmission (Chaston and Goodrich-Blair, 2010). In terms of evolution, it was suggested that episymbiosis represents a more primitive stage than endosymbiosis (Dubilier et al, 2008).…”
Section: Epibiont Diversity and Acquisitionmentioning
confidence: 99%
“…The egg mucus interface probably facilitated attraction, accumulation and host recognition of epibionts for horizontal transmission. This epibiont transmission pathway is in adequacy with the large colonization of the MAR by R. exoculata because horizontal transmission is supposed to promote dispersal as compared with vertical transmission (Chaston and Goodrich-Blair, 2010). In terms of evolution, it was suggested that episymbiosis represents a more primitive stage than endosymbiosis (Dubilier et al, 2008).…”
Section: Epibiont Diversity and Acquisitionmentioning
confidence: 99%
“…1A). The importance of chitin in the chemical dialogue between squid and vibrio is reminiscent of the contribution of host glycans and structural polysaccharides to other host-microbe interactions (9). For example, (i) the catabolism of exoskeleton-derived chitin by Vibrio cholerae enhances transmission from an invertebrate vector to a susceptible host (25), (ii) pectin catabolism by the plant pathogen Xylella fastidiosa promotes transmission to leafhopper vectors (26), and (iii) foraging of mammalian mucin-derived glycans, such as fucose and sialic acid, forms a nutritional scaffold for the gut microbiota (27)(28)(29).…”
Section: Significancementioning
confidence: 99%
“…First, the provision of nutrients such as host-derived glycans contributes to the microbial community structure and is a source of microbederived metabolites such as short-chained fatty acids (SCFA) that promote the maturation of local and systemic immune functions (6)(7)(8)(9). Second, the nutritional and environmental changes that mark the developmental trajectory of an organism from its juvenile to adult form are accompanied by distinct shifts in both the composition and functions of the maturing host's microbiota (10,11).…”
mentioning
confidence: 99%
“…For instance, co-evolution or codivergence of bacteria and their hosts has been extensively studied in vertically transmitted associations, and can involve events like gene sharing and genome reduction within the microbial partner(s) (Kikuchi et al, 2009;Moran and Bennett, 2014). Similarly, horizontally transmitted symbioses of plants and invertebrates have offered the opportunity to examine the evolution of species specificity, revealing evidence for strategies such as congruent evolution and partner choice (Chaston and Goodrich-Blair, 2010;Sudakaran et al, 2015). In the symbiosis between the squid Euprymna scolopes and the luminous bacterium Vibrio fischeri, as in other environmentally acquired, non-obligatory symbionts, one can experimentally expose an aposymbiotic host to genetically distinct V. fischeri strains, either singly or in combination, and monitor the establishment and dynamics of the resulting symbiont population.…”
Section: Introductionmentioning
confidence: 99%